Pengaruh Gum Arab Pada Minuman Madu Sari Apel Ditinjau Dari Mutu Organoleptik, Warna, pH, Viskositas, dan Kekeruhan (Jurnal Ilmu dan Teknologi Hasil Ternak, 2015)
Apple concentrated honey drink was modified product from fresh honey with apple concentrated to increase the taste, but there was aglutination because of pectin and tannin in apple concentrated and needed stabilizer as gum arabic. The purpose of this research was to find out the best consentration of gum arabic on apple concentrated honey drink in terms of taste, arorganoleptic (taste and aroma), color (L*, a*, b*), pH, viscosity, and turbidity. The treatments were without gum arabic (P0); gum arabic 0.05% (P1); gum arabic 0.1% (P2); and gum arabic 0.15% (P3). The method of this research was experiment with Completely Randomized Design (CRD) by using 4 treatment and 4 times replication. The data were analyzed by ANOVA and would be continued by Duncan’s Multiple Range Test (DMRT). The result of this research showed that consentration of gum arabic gave highly significant different effect on aroma, pH, viscosity, and turbidity, gave significant different effect on yellowness (b*), and gave no different effect on taste, lightness (L*) and redness (a*). Conclusion of this research was the adding of gum arabic 0.15% (P3) on apple concentrated honey drink gave the best quality of apple concentrated honey drink for taste 4.54±0.65, aroma 6.00±1.01, lightness (L*) 21.73±0.43, redness (a*) 9.78±0.76, yellowness (b*) 5.68±0.80, pH 6.68±0.13, viscosity 1.112±0.003 cP, and turbidity 165.13±1.55 NTU.